The Probability Analysis and Factors Affecting the Decision to Switch to Online Examination of Souphanouvong University: https://doi.org/10.69692/SUJMRD0901178 - Mekthanavanh, Vinath; Siphada, Vatthanaly; Keopaseuth, Pathoumphone; Manivanh, Vialakone; Soukchaleun, Xaysavath (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research aims to analyze the probability and the factors attracting for the use of an online examination in each semester of Souphanouvong University. The switching mode to online mode is not only to respond to the situation of Covid-19 pandemic, it is also to examine the possibility for the long-term success. We utilized the efficiency model and steps of an online examination in Google Form based on user experiences in domestic and foreign countries. We implemented the following steps: separated the question page into several sections, defined a password for the student, avoid showing the number of questions, randomizing the questions and answers, limited the number of questions in each page, hid the answer after the exam was submitted, imposed a deadline and closed the link automatically, defined the specific number of submissions and hid the link of re-submission. There are 93 teachers and 180 students included in the samples. The result of the statistical analysis showed that the teacher readiness to use online examinations is high , while the budget and classroom-equipment readiness are averages and , respectively. The satisfaction level of students for online exam implementation is high. However, the proportion of students who are unsatisfied is only 13.9%. The summarization results of 6 factors reveals a satisfactory level ( . Our results demonstrate that Souphanouvong University’s online examination has a high probability of being used